Does Mineralocorticoid Receptor Antagonism Prevent Calcineurin Inhibitor-Induced Nephrotoxicity? - Mortensen, Line Aas; Bistrup, Claus; Thiesson, Helle Charlotte (Frontiers in Medicine, 2017)
Calcineurin inhibitors (CNI) have markedly reduced acute rejection rates in renal transplantation, thus significantly improved short-term outcome. The beneficial effects are, however, tampered by acute and chronic nephrotoxicity leading to interstitial fibrosis and tubular atrophy, which impairs long-term allograft survival. The mineralocorticoid hormone aldosterone induces fibrosis in numerous organs, including the kidney. Evidence from animal models suggests a beneficial effect of aldosterone antagonism in reducing CNI induced nephrotoxicity. This review summarizes current evidence of mineralocorticoid antagonism in animal models of CNI induced nephrotoxicity and the results from studies of mineralocorticoid antagonism in renal transplant patients.